Chordoid Meningioma: Literature Review - Massella Junior, Carlos Roberto; de Morais, Marcus Vinicius; Figueiredo, Rafael Pontes; Morales, Andrezza Garcia; Porto de Melo, Paulo Mácio (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Chordoid meningiomas (CMs) are a rare subgroup of tumors, accounting for ∼ 0.5% of all meningiomas. Chordoid meningioma tumors correspond to World Health Organization (WHO) Grade II lesions and behave aggressively, with an increased likelihood of recurrence. There are few genetic studies about CMs, but we understand that there is deletion at many chromosomal loci. Histologically, CMs are characterized by strands and cords of meningothelial cells arranged in a mucinous stroma. Morphologically, it can mimic other chondroid and myxoid tumors within the brain and its vicinity, thus posing a diagnostic challenge. Chordoid meningiomas have an aggressive clinical course and a propensity to recur compared with classical meningiomas. The goal of the treatment is surgery, with total resection of the tumor; however, due to its high degree of recurrence, radiotherapy is often necessary as an adjuvant treatment.
Keywords: meningioma; chordoid; brain neoplasms; pathology